Picking up flexible pieces out of a bundle. - Doulgeri, Z. (IEEE Robotics and automation magazine)
The paper describes a robotic-arm gripper with soft-tipped fingers to perform human-like grasps of flexible material pieces out of an unordered bundle. The primary purpose is to achieve the stability and robustness of a human-like grasp with a simple and cost-effective gripper. The work has been stimulated by the handling problem present in the fur-tanning industry